Formation of Carbon-Silicon Bond and Effect of Silicon on Organic Reactions (Journal of Engineering Science, 2020)
In this work, we report carbon-silicon bond formation in thiophene, assisted with alkylated silylchloride. The formylation reaction of silylated thiophene has been discussed and achieved 61% overall yield of reactions. The compounds obtained are characterized quantitatively and qualitatively by using elemental analysis, FT-IR spectroscopy, UV/Visible spectroscopy, and proton NMR spectroscopy. This research work will boost chemists to make the carbon-silicon bond and utilize them in various applications.Journal of Engineering Science 11(1), 2020, 101-105